The Relationship Between Knowledge And Family Support With Adherence To Taking Medication For Hypertension Patients At The Jambi Police Biddokkes Pratama Polyclinic - Septiani, Dian Mariza; AZ, Rasyidah; Octavia, Dian (Journal Hygeia Public Health, 2025)
Background: Hypertension is a chronic disease that requires long-term medication adherence. Patients’ compliance is often influenced by their knowledge and family support. Objective: To determine the relationship between knowledge and family support with medication adherence among hypertensive patients at Poliklinik Pratama Biddokkes Polda Jambi.Methods: This study used an analytical design with a cross-sectional approach. The sample consisted of hypertensive patients undergoing regular treatment. Data were collected through structured questionnaires and analyzed using the chi-square test.Results: The study found that most patients with high knowledge and good family support were more adherent to medication. There was a significant relationship between knowledge (p < 0.05) and family support (p < 0.05) with medication adherence.Conclusion: Patient knowledge and family support significantly influence medication adherence in hypertensive patients. Educational interventions and family involvement are essential to improve patient compliance.